USING INDICATOR FAUNA ELEMENTS IN BIOTOPE MAPS FOR URBAN LANDSCAPE PLANNING - Sözgen, Omer Taha; Aksu, Gül Aslı; Oğurlu, Idris; Ayaşlıgil, Tülay Erbesler (LIFE: International Journal of Health and Life-Sciences, 2020)
With the developing technology and increasing population, cities are rapidly and unplanned growing around the world and therefore the natural environment and species are under threat. To eliminate the negative effects of this treatment, qualified tools and data are needed to make appropriate planning decisions. To benefit from the biotope maps, which are important data sources, they should be prepared rapidly in parallel with the speed of urbanization. Detection of sensitive ecosystems in urban landscapes can be achieved by mapping biotopes. These maps are also important for the development, management, and continuity of ecological infrastructures. From this point of view, to obtain a biotope map that will be prepared for urban landscape planning, it is thought that the determination of the required biotope classes with indicator fauna elements may be more practical. In this study, the literature based on indicator fauna elements was examined and evaluated concerning urban landscape planning. As a result, it was determined that biotope maps, prepared based on indicator fauna elements, could be obtained rapid and qualified data.